Analisis Kebutuhan Biaya dan Pemanfaatan Pertolongan Persalinan Bagi Keluarga Miskin di Kabupaten Indramayu Tahun 2006 - Yadi Hidayat (Lembaga Penelitian Sekolah Tinggi Ilmu Kesehatan Kuningan, 2012)
Introduction: The government has given a health service for poor family (Gakin) by PKPS-BBM health-aspect program to overcome the health problem which emerges as an economic crisis impact, such as given the expense of helping child birth by midwife is equal to 150.000 rupiahs. The used of helping childbirth cost is still lower. Becouse of this, the writer wants to know how much setcost of helping childbirth and also its used by Gakin. Methods: This research is a quantitative research by conducting an economic analysis of child birth cost requirement for Gakin and also conducting a Rapid Survey to know the used of helping child birth by poor family and also the factor that related to help child birth. A qualitative research is used to get the answer or deep information, such as countryside midwife perception in conducting childbirth help, cost sufficiency of helping childbirth and cost mechanism of helping childbirth. Results: The research result indicates that cost of helping childbirth which available with requirement is equal to 213.250 rupiahs. Gakin who has been used childbirth by the midwives are almost 69,9%. From midwife factor as provider which affected the used of helping childbirth becouse substitution cost for helping childbirth of Gakin is low relatively and long duration of cost liquefaction process of helping childbirth. From childbirth mother factor of Gakin, as a factor which affected the lower of using a child birth by midwife such as: ignorance of Gakin that child birth by midwife is not getting charge and they are worry to pay high cost if they are helped by a midwife. Discussion: From marginal result of this research, it was suggested to goverment and society efforts to improve the health service access for Gakin, especially the service of helping child birth by adjustment return the cost of helping child birth which is available with requirement, facilitating the cost liquefaction mechanism of helping child birth, socialization concerning Gakin rights to get helth service and also the improvement of midwife performing in countryside.